Dysbiosis and Variation in Predicted Functions of the Granulation Tissue Microbiome in HPV Positive and Negative Severe Chronic Periodontitis. (14th April 2019) - Chowdhry, Rebecca; Singh, Neetu; Sahu, Dinesh Kumar; Tripathi, Ratnesh Kumar; Mishra, Archana; Singh, Anjana; Mukerjee, Indrashis; Lal, Nand; Bhatt, Madan Lal Brahma; Kant, Ravi
Abstract : Retrospective analysis has already shown correlation between severe Chronic Periodontitis (CP) cases with human papiloma virus (HPV). Hence, we aimed to explore deep-seated infected granulation tissue removed during periodontal flap surgery procedures for residential bacterial species between HPV+ and HVP- CP cases, which may serve as good predisposition marker for oral cancer. All CP-granulation samples showed the prominence of Firmicutes, Proteobacteria, and Bacteroidetes phyla with an abundance of gram negative anaerobes, except Streptococcus . In Beta diversity nonmetric multidimensional scaling plot, the random distribution of species was observed between HPV+ and HPV- CP granulation-samples. However, an abundance of Capnocytophaga ochracea was observed in HPV+ CP samples (p<0.05), while Porphyromonas endodontalis, Macellibacteroides fermentas, Treponema phagedenis, and Campylobacter rectus species were highly abundant in HPV- CP samples (p<0.05). The differential species richness leads altered functions related to mismatch-repair and nucleotide excision-repair and cytoskeleton-proteins. Hence, differential abundance of gram negative bacterial species between HPV+ and HPV- granulation-samples under anaerobic conditions may release virulence factors which may alter pathways favouring carcinogenesis. Hence, these species may serve as good predisposition marker for oral-cancer.